Organizational Brand of a Military Institution - Sabado, Frisiana (ABAC ODI JOURNAL Vision. Action. Outcome, 2016)
Abstract This study conceptualized organizational brand as a package of instrumental and symbolic attributes. This framework was used to formulate hypotheses to examine the brand of the Philippine Military Academy in terms of its attractiveness. The relative importance of instrumental and symbolic brand beliefs were examined across different groups of actual applicants: those who live most of their civilian life in rural country side and urban city. This study aims to contribute to an increased knowledge of the factors influencing organizational attraction and adds a new marketing-based angle in the recruitment process and retention of military personnel. Results show that a combination of instrumental and symbolic attributes determines the brand of the Philippine Military Academy. The study revealed that perceptions on instrumental and symbolic attributes of the Philippine Military Academy do not make the academy more or less attractive for applicants from rural country side and from urban cities because the differences of applicant’s perceptions are not significant. Keywords: Brand, Instrumental, Symbolic, Recruitment, Retention